Analisis Program Badan Usaha Milik Desa di Desa Melati II Kecamatan Perbaungan - Sasmita Siregar; Bagus Setiawan; Desi Novita (Universitas Medan Area, 2023)
Not all BUMDes go well and some even walk on the spot. Quality human resource skills are needed in the development of BUMDes programs. This research aims to analyze the development of BUMDes and what are the businesses carried out by BUMDes in Melati II village, Perbaungan Subdistrict. The location of this research is in Melati II Village perbaungan subdistrict. Determination of the number of samples using sampling quota with the sample number of 36 people. Data analysis methods use descriptive analysis. The results showed that when viewed in terms of economic dimensions showed that as many as 69.4% of respondents rated that BUMDes in Melati II village were going very well. This is proven by the management of irrigation saluraan into the agricultural tourism sector, so that the condition of rice fields becomes more well organized. It can be concluded that the development of BUMDes in Melati II village is relatively good. This is seen from respondents' answers about several indicators of bumdes development, namely social dimension, environmental dimension, economic dimension and management dimension is in the category of good - very good.In carrying out its program, BUMDes utilize th